Synthesis, biological evaluation and mode of action studies of novel amidinourea inhibitors of hepatitis C virus (HCV) - Magri, A; Mokrane, O; Lauder, K; Patel, A; Castagnolo, D (Elsevier, 2019)
Novel amidinourea derivatives have been synthesised and evaluated for their antiviral activity against Hepatitis C Virus (HCV). A compound with an amidinourea-spermine chemical structure, different from that of standard anti-HCV drugs, showed micromolar activity against HCV and excellent viability. Studies on the mode of action revealed that the new compound may act against HCV through the inhibition of IRES-mediated translation.